PyroTyping, a novel pyrosequencing-based assay for Mycobacterium tuberculosis genotyping - B. Molina-Moya (Nature Portfolio, 2017)
Abstract We developed a novel method, PyroTyping, for discrimination of Mycobacterium tuberculosis isolates combining pyrosequencing and IS6110 polymorphism. A total of 100 isolates were analysed with IS6110-restriction fragment length polymorphism (RFLP), spoligotyping, mycobacterial interspersed repetitive units – variable number tandem repeats (MIRU-VNTR), and PyroTyping. PyroTyping results regarding clustering or discrimination of the isolates were highly concordant with the other typing methods performed. PyroTyping is more rapid than RFLP and presents the same discriminatory power, thus, it may be useful for taking timely decisions for tuberculosis control.